Risk Analysis to Improve Procurement Time Performance of the Construction Services Project of Air Traffic Control (ATC) Tower and Supporting Facilities - Prabowo, Bagus Adi; Isvara, Wisnu; Rachmawati, Titi Sari Nurul (Avenew Indonesia, 2026)
The implementation of the procurement process for the construction services of the ATC Tower and Supporting Facilities at Perum XYZ is expected to be completed on time with the delivery of the ATC Tower infrastructure and Supporting Facilities to support optimal flight navigation services. However, in the period 2016-2023, obstacles occurred at several project locations which caused the benefits of the project development to be delayed. This study aims to analyze the dominant risk factors that affect the performance of the procurement time for the construction services of the ATC Tower and Supporting Facilities at Perum XYZ. Risk identification was carried out through literature studies and then validated by experts. Furthermore, the risks were submitted to respondents who had been involved in the procurement of construction services for the ATC Tower and Supporting Facilities at Perum XYZ and then a risk analysis was carried out by referring to the company's internal regulations related to the Company's Risk Management Policy and Guidelines. From the results of data collection and analysis, it was found that there were 5 dominant risk factors with a high risk level that affected the procurement time performance. The results of this study can be a basis for determining the development of a procurement strategy for the construction services of the ATC Tower and Supporting Facilities at Perum XYZ in improving procurement time performance